A SYSTEM OF EXERCISES TO DEVELOP CRITICAL THINKING IN MOTHER LANGUAGE LESSONS - Erkinova Gulsanam Otabek kizi (International Journal of Literature and Language Studies, 2026)
This article discusses the theoretical and practical foundations of a system of exercises that serve to develop students' critical thinking competence in native language lessons. The article analyzes the pedagogical content of the concept of critical thinking, its role in native language education, and its inextricable link with Bloom's taxonomy, the competency-based approach, and interactive methods. It is argued that the proposed exercises serve to develop students' logical, analytical, and creative thinking. The results of the article can be used as methodological recommendations in organizing native language lessons in secondary educational institutions.